2007
DOI: 10.2172/965609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exothermic Reactions from Bulk-Vitrification Melter Feeds Containing Cellulose

Abstract: SummaryThe baseline bulk-vitrification (BV) process (also known as in-container vitrification ICV™) includes a mixer/dryer to convert liquid waste into a dried, blended feed for vitrification. Feed preparation includes blending liquid low-activity waste (LAW) with glass-forming minerals and cellulose and drying the mixture to a suitable dryness, consistency, and particle size for transport to the ICV TM container.This drying process is conducted under vacuum in the temperature range of 60 to 80°C. The nominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As in previous work (Scheele et al 2008), the initial reaction is endothermic and begins essentially immediately and is likely the loss of the 4 wt% water. It is followed by a small exothermic reaction at 290°C and two stronger exothermic reactions beginning at 300 and 380°C.…”
Section: Bv Feed Tg/dta/ftir Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…As in previous work (Scheele et al 2008), the initial reaction is endothermic and begins essentially immediately and is likely the loss of the 4 wt% water. It is followed by a small exothermic reaction at 290°C and two stronger exothermic reactions beginning at 300 and 380°C.…”
Section: Bv Feed Tg/dta/ftir Resultssupporting
confidence: 58%
“…For the isothermal testing, we used the ARC, used in our earlier thermal sensitivity studies (Scheele et al 2008), in its isothermal mode. The ARC is an adiabatic calorimeter originally developed by Dow Chemical to determine safe process operating temperatures for tested materials.…”
Section: Isothermal Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This article provides results from our probative set of thermoanalytical experiments performed in support of the Technical Advisory Team's assessment to identify the internal waste reaction(s) that under WIPP conditions could have led to the drum breach and radionuclides release. Using CCPS recommendations [17,18] and our previous experience investigating reaction thermal sensitivities of 1) cellulose and different nitrate salt mixtures [5,6,8,20,21] and 2) amine-based complexants and nitrate mixtures [22] as our investigative foundation, we used simultaneous thermogravimetric and differential thermal analysis (TG/DTA) and accelerating rate calorimetry (ARC) to determine the thermal sensitivities of a selected set of waste constituents, simulated remediation products, and simulated remediation wastes. The simulant compositions were based on the multi-component composition of the mixture of the original Los Alamos liquid and salt TRU waste, remedial additives, and other materials that were put into the drum.…”
Section: Figure 1 Wipp Drum After Breachmentioning
confidence: 99%
“…For example, Beitel investigated the explosivity and combustibility of various organics with nitrate-rich Hanford salt cake waste and nitrate salts Beitel 1976a;Beitel 1976b;Beitel 1976c]. Scheele and coworkers investigated the reactions of amine-based complexants, carboxylate-based complexants, cellulose, and sucrose with nitrate and/or nitrite salts and simulated Hanford nitrate-rich wastes [Scheele 1995;Scheele 2005;Kim 2005;Scheele 2008], and the Bureau of Mines investigated the reactivity and explosivity of amine-and carboxylate-based complexants with nitrate and/or nitrite salts [Turner 1994b;Turner 1994a]. ww Findings from these studies revealed that mixtures of nitrates and organics having many constituents can have lower onset temperatures than that of pure mixtures indicating the possibility of synergistic and catalytic effects of the constituents.…”
Section: Chemical Hydrolysis and Oxidation Of Organicsmentioning
confidence: 99%